An Energy Efficient Task Scheduling Algorithmic approach using PK-Leach for dynamic offloading - Dr.SK.Piramu Preethika (International Journal of Advanced Science and Technology, 2020)
The capability to estimate the circumstances and ability to solving the complexity is a delicate task to carry out. In a real situation dynamic offload collaborate a vital role to transfer the essential things to a remote server and preserve the data loss is a challenging task. Dynamic offloading will be functioned when energy drop is heavier then data packets would be moved to cluster to capture the data without loss. This study proposes an energy efficient task scheduler algorithm and PK-LEACH method to choose the cluster head and transfer the information among the cluster heads to safeguard the network lifeline and maintains the energy depletion.